Peranan Tokoh Intelektual Muda dalam Perkembangan Politik di Indonesia pada Era Digital - Annisa Vira; Pulung Sumantri; Abdul Azis (Polyscopia, 2024)
Democracy's vitality in a nation hinges on the depth of political engagement, evident when the populace actively participates in events like presidential and regional elections. The level of political involvement serves as a pivotal gauge for a country's democratic progress, reflecting genuine concern for political development. This engagement, influenced by diverse societal groups, notably the youth, holds significance. Generation Z and Millennials, the key demographics, wield considerable influence, with Generation Z earning the moniker "the mobile generation" due to a 93.9 percent internet dependence. Meanwhile, Millennials, with an 88.4 percent reliance on the internet, grapple with career pursuits. In politics, the youth are coveted assets, pivotal in election contests for state leaders, regional heads, or representatives, given their distinct voices and impact on societal dynamics.